2014
DOI: 10.1128/jb.01376-13
|View full text |Cite
|
Sign up to set email alerts
|

PvdP Is a Tyrosinase That Drives Maturation of the Pyoverdine Chromophore in Pseudomonas aeruginosa

Abstract: eThe iron binding siderophore pyoverdine constitutes a major adaptive factor contributing to both virulence and survival in fluorescent pseudomonads. For decades, pyoverdine production has allowed the identification and classification of fluorescent and nonfluorescent pseudomonads. Here, we demonstrate that PvdP, a periplasmic enzyme of previously unknown function, is a tyrosinase required for the maturation of the pyoverdine chromophore in Pseudomonas aeruginosa. PvdP converts the nonfluorescent ferribactin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…4). In a more recent study on PvdP, it was already suggested that PvdN, besides PvdM and PvdO, can only be involved in sidechain modifications, as PvdP promotes all steps of chromophore formation (8). Our study now shows that this suggestion was indeed correct.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…4). In a more recent study on PvdP, it was already suggested that PvdN, besides PvdM and PvdO, can only be involved in sidechain modifications, as PvdP promotes all steps of chromophore formation (8). Our study now shows that this suggestion was indeed correct.…”
Section: Discussionsupporting
confidence: 69%
“…Double crossover mutants were selected by successive counter-selection on sucrose-containing medium, and scar-and marker-less deletions were identified and confirmed by PCR and sequencing. We included a deletion of monocistronic pvdP as control, as PvdP has been biochemically confirmed to be essential for the fluorophore formation (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferribactins are transported into the periplasm in acylated form and deacylated thereafter by PvdQ (3)(4)(5). In the periplasm, a 5,6-dihydroxyquinoline fluorophore is generated from ferribactin and the conserved glutamic acid residue at the first position of the peptide is modified (6)(7)(8). Iron can then be chelated by the two hydroxyl groups of the fluorophore and four further ligands from side chains of the peptide moiety (9,10).…”
Section: Discussionmentioning
confidence: 99%